(untitled) (Diametros, 2025)
Materialism as a doctrine is, of course, a part of the history of philosophy, even if it was often a polemical construct, and it took until the 18th century for philosophers to be willing to call themselves materialists. Difficulties also have been pointed out in terms of “continuity,” i.e., does what Democritus, Lucretius, Hobbes and Diderot have to say about matter, the body and the soul all belong in one discursive and conceptual frame? Interestingly, materialism is also a classic figure in the history of medicine, often intersecting with philosophical considerations. Notably, the question of body-soul relations. This is apparent in Galen’s treatise on body and soul and then much more massively in the early modern period (with reference to Galen, but also Lucretius, and Aristotelian naturalism). In the following essay I reflect on the exact nature of early modern medical materialism, its philosophical status and contribution.